Effects of simulated and real altitude exposure in elite swimmers - Robertson, E. Y.; Aughey, R. J.; Anson, J. M.; Hopkins, W. G.; Pyne, D. B. (The Journal of Strength and Conditioning Research, 2010)
The effect of repeated exposures to natural and simulated moderate altitude on physiology and competitive performance of elite athletes warrants further investigation. This study quantified changes in hemoglobin mass, performance tests, and competitive performance of elite swimmers undertaking a coach-prescribed program of natural and simulated altitude training. Nine swimmers (age 21.1 ± 1.4 years, mean ± SD) completed up to four 2-week blocks of combined living and training at moderate natural altitude (1,350 m) and simulated live high-train low (2,600-600 m) altitude exposure between 2 National Championships. Changes in hemoglobin mass (Hbmass), 4-mM lactate threshold velocity, and 2,000 m time trial were measured. Competition performance of these swimmers was compared with that of 9 similarly trained swimmers (21.1 ± 4.1 years) who undertook no altitude training. Each 2-week altitude block on average produced the following improvements: Hbmass, 0.9% (90% confidence limits, ±0.8%); 4-mM lactate threshold velocity, 0.9% (±0.8%); and 2,000 m time trial performance, 1.2% (±1.6%). The increases in Hbmass had a moderate correlation with time trial performance (r = 0.47; ±0.41) but an unclear correlation with lactate threshold velocity (r = -0.23; ±0.48). The altitude group did not swim faster at National Championships compared with swimmers who did not receive any altitude exposure, the difference between the groups was not substantial (-0.5%;±1.0%). A coach-prescribed program of repeated altitude training and exposure elicited modest changes in physiology but did not substantially improve competition performance of elite swimmers. Sports should investigate the efficacy of their altitude training program to justify the investment.